Performance of Submerged Membrane Bioreactor Combined with Powdered Activated Carbon Addition for the Treatment of an Industrial Wastewater - Widjaja, Tri; Altway, Ali; Soeprijanto, Soeprijanto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Membrane technology is one of the alternative solutions to overcome industrial wastewater treatment developed nowadays. The addition of PAC (Powdered Activated Carbon) in the activated sludge using Submerged Membrane Adsorption Hybrid Bioreactor (SMAHBR) is expected to increase the organic material removal. The purpose of this study was to determine the performance of submerged membrane bioreactor and activated carbon adsorption capacity of organic materials in wastewater. This study used SIER (Surabaya Industrial Estate Rungkut â€“ Surabaya, Indonesia) waste as activated sludge operated at Mixed Liquor Suspended Solid (MLSS) concentrations of 8000 and 15000 mg/l, and Chemical Oxygen Demand (COD) concentrations of 1500, 2500 mg/l, Sludge Retention Time (SRT) of 10;20; and 30 days and activated carbon variables of 0%; 2.5%; 5%; 7.5%; 10%. The results showed that the fouling potential occurred at high MLSS where the COD removal occurred at PAC addition of 10% reaching 91.86%. High Soluble Microbial Product (SMP) accumulation (Â± 10 mg/l) occurred in short SRT and high MLSS concentration. PAC addition resulted in decreased microorganisms in the reactor and better effluent of SMAHBR, as a result, the performance of the submerged membrane bioreactor would be restored.